Anonymous Blockchain based model for e-Voting - Taneska, Marija; Halimi, Fat (My University, 2022)
In this paper, we analyze the provided security, anonymity, and privacy provided by Zcash and Monero. We focus on the description for the e-voting framework based on Zcash and Monero using their anonymity advantages. Analyzing advantages and disadvantages of Zcash and Monero, we make comparation between them, and conluded that Monero is more secure than Zcash, and we recommend using Monero for serious e-Votings. Our key is to give a sparkle to Blockchain developers to create a legitimate framework or system that would be based on Zcash and Monero Blockchains to realize e-voting.
Keywords: e-voting, Blockchain, Zcash, Monero